1983
DOI: 10.1126/science.222.4621.327
|View full text |Cite
|
Sign up to set email alerts
|

Zonal Winds in the Central Equatorial Pacific and El Niño

Abstract: Easterly trade winds from near-equatorial islands in the central Pacific weakened before each El Niño between 1950 and 1978, except for the 1963 El Niño. The weakening of the easterlies and their later collapse did not occur uniformly over several months, but rather through a series of strong westerly wind bursts lasting 1 to 3 weeks. The bursts may force equatorial Kelvin waves in the ocean that can both initiate and sustain the sea surface warming characteristics of El Niño events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(99 citation statements)
references
References 23 publications
3
94
0
1
Order By: Relevance
“…The increased occurrence of WWBs prior to and during most El Niño events has been observed and noted in the past (e.g., Delcroix et al 1993;Keen 1982;Luther et al 1983;Vecchi and Harrison 2000;Verbickas 1998). We begin here with an analysis of high-resolution satellite observations suggesting that WWBs are indeed affected by ENSO.…”
Section: Observational Evidence Of Wwb Modulation By Ensomentioning
confidence: 85%
See 1 more Smart Citation
“…The increased occurrence of WWBs prior to and during most El Niño events has been observed and noted in the past (e.g., Delcroix et al 1993;Keen 1982;Luther et al 1983;Vecchi and Harrison 2000;Verbickas 1998). We begin here with an analysis of high-resolution satellite observations suggesting that WWBs are indeed affected by ENSO.…”
Section: Observational Evidence Of Wwb Modulation By Ensomentioning
confidence: 85%
“…It therefore makes sense to expect that WWBs may be involved with the onset of El Niño events (Latif et al 1988; Lengaigne et al 2004;Luther et al 1983;Perigaud and Cassou 2000). Indeed, WWBs have been observed to occur in association with the onset of every significant El Niño event for the past 50 years (Kerr 1999;McPhaden 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, because two out of these seven cases had very strong westerly winds (15ms-1 in one case and 20ms-1 in another case), this study will present results related to these two bursts. It was noted that some other westerly episodes were present in the equatorial central Pacific near 170*W during 1970-73 (e.g., Luther et al, 1983). Because the daily surface wind data in that region were not yet available to us, the present study only focuses on the short-term impact of the extratropical forcing on wind variations in the EWP and does not concentrate on the region further east.…”
Section: Data Sources and Selection Of Study Periodsmentioning
confidence: 99%
“…Over the central Pacific (*170*E to 170*W), these anomalies (i.e., not necessary to be westerly flows) are impulsive in nature and last from one to three weeks (Luther et al, 1983). These surface westerly surges generate oceanic Kelvin waves which in turn may cause the warming of the sea surface in the eastern equatorial Pacific (e.g.., Wyrtki, 1975;McCreary, 1976;Philander, 1981;Lukas et al, 1984;Harrison and Schopf, 1984;Cane and Zebiak, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Keen (1982) analyzed cyclone pairs developed in the equatorial western Pacific and pointed out their important role in ENSO by maintaining and expanding the warm equatorial sea surface temperature (SST) anomaly. Luther et al(1983) demonstrated that the westerly wind bursts occur intermittently leading up to the El Nino onset.…”
Section: Introductionmentioning
confidence: 99%